Projected impact on labour productivity costs of cancer-related premature mortality in Europe 2018–2040 - Ortega Ortega, Marta; Hanly, Paul; Pearce, Alison; Soerjomataram, Isabelle; Sharp, Linda (Applied Health Economics and Health Policy, 2023)
2023 Acuerdos transformativos CRUE Aim To estimate the potential cost of lost labour productivity due to cancer-related premature mortality in Europe (EU-27 plus Norway, Switzerland, Iceland and United Kingdom) from 2018 to 2040. Methods Deaths and years of potential productive life lost due to 23 types of cancer were estimated for 2018–2040, for 31 European countries. The data were analysed by age groups, by sex and by year. Projected productivity costs were estimated by calculating gross earnings by country, gender and age group using the Human Capital Approach, adjusting for projected labour force participation and unemployment rates. Various data sources were used. Sensitivity analyses were conducted. Results Between 2018 and 2040, cancer is expected to cause around eight million premature deaths (58% male). The cumulative projected productivity costs in this respect are €1.3 trillion, representing an annual average of €58.7 billion, or 0.43% of the EU-27 gross domestic product. Labour productivity costs are projected to decrease by 6% from 2018 to 2040. The highest cost region is Western Europe, where Germany and France will experience the highest cumulative losses (€288 and €192 billion, respectively). The most costly cancers, in terms of total costs related to productivity losses, are of the lung and colorectum (€264.4 and €116.3 billion, respectively). In terms of average productivity cost per death, the most costly forms of cancer are Hodgkin lymphoma (€301,157) and melanoma (€260,522). Conclusion The novel information presented could help national policymakers anticipate possible areas for cost savings. Action should be taken on disease prevention, on reducing mortality and on delaying the age of death due to Hodgkin lymphoma, brain cancer, leukaemia and melanoma. Furthermore, the study findings enhance our understanding of macroeconomic variables and could be useful in determining a re-allocation of health expenditures. Asociación de Economía de la Salud (España) Universidad Complutense de ...